Analisis Estetika Motif Karawo Gorontalo Dengan Kajian Pola, Makna, Dan Bahasa Visual Dalam Perspektif Bahasa Indonesia - Agustin, Puspita Dian; Mbeoga, Jandriawan; Bagu, Fandu Febrian; Dai, Alisha Yulyana; Padungo, Adha; Rauf, Apriliani; Liputo, Cindrawaty; Musa, Fadila; Solihin, Juliete Zharen L.; Katili, Nindi Aprilia; Igirisa, Nadia Nur Aulliah; Husain, Nurul Salsabil; Hasan, Nur Sintia; Yahya, Shoviyani; Dolu, Sulfiani (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study analyzes the aesthetics of karawo motifs, a distinctive Gorontalo embroidery art, from the perspective of Indonesian Language, focusing on patterns, meanings, and visual language. A qualitative descriptive approach was employed through observation, interviews with artisans from Karawo Naga Mas in Mongolato Village, Telaga Jaya Subdistrict, and documentation to reveal the consistency of traditional patterns like the flower bud motif that adapts to modern trends, cultural symbolism such as beauty and fertility, and visual elements of lines, shapes, colors, and repetitions forming Gorontalo's identity. The findings indicate that karawo's aesthetics integrate innovative patterns, symbolic meanings, and visual language as a medium for cultural communication supporting local heritage preservation.​